Edukasi dan Penyuluhan Diabetes Mellitus Kepada Masyarakat Desa Empat Balai Kecamatan Kuok Kabupaten Kampar Riau - Husnawati, Husnawati; Susanty, Adriani; Sari, Seftika; Thamrin, Thamrin; Suheri, Wira Noviana; Izrawati, Izrawati; Delvi, Kasma Muria; Dirmaningsih, Septi; Ngazizah, Yeti Nur; Meridona, Meridona; Sandi, Widya Ari (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
Diabetes Mellitus (DM) is a non-communicable disease with increasing prevalence, particularly in rural areas with limited access to health information and services. This community service activity aimed to improve the knowledge of residents in Empat Balai Village, Kuok Subdistrict, Kampar Regency, Riau, regarding DM, its risk factors, and prevention efforts through an educational and participatory community-based approach. The method involved direct counseling, group discussions, and pre-test and post-test assessments to evaluate participants' understanding. The results indicated a significant improvement in knowledge, with the average score increasing from 6.7 (pre-test) to 8.98 (post-test). The education program successfully dispelled common myths, raised awareness of healthy lifestyles, and fostered positive perceptions of both medical and non-medical treatment options. The enthusiastic response from the community demonstrated the effectiveness of this approach in promoting health and preventing non-communicable diseases. This activity highlights the importance of collaboration between students, healthcare workers, and local authorities in public health education and the need for sustained outreach programs.